UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOLIK KULIT BUAH JERUK NIPIS (Citrus aurantifolia) DENGAN METODE DPPH (1,1-difenil-2- pikrilhidrazil) - Ismiyyatun Khasanah; Maria Ulfah; Sumantri Sumantri (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2014)
ABSTRACTCitrus aurantifolia is known contains flavonoid compound and high Vitamin C. One of theeffects of flavonoid and Vitamin C are antioxidant. This research aims to knowing the antioxidantactivity of citrus aurantifolia etanolic extract by using the DPPH (1, 1-difenil-2-pikrilhidrazil) methodand to knowing the active compound that containing whithin.The research was done by making level series of citrus aurantifolia etanolic extract, they were10, 20, 40 and 80 μg/ml. As a standard of comparison was used vitamin C with concentrations 1, 2, 4and 8 μg/ml. As a blank was used DPPH 0,1 mM. The antioxidant activity test was done by the DPPHmethod. The achieved data was counted to know it’s antioxidant activity. The statistical analysis wasused T-Test. To know IC50 (Inhibition Concentration)50 was used the probit analysis and to know it’sactive compound content was done an identification with TLC (Thin Layer Chromatography).The result of the research shows that etanolic extract of citrus aurantifolia has antioxidantactivity IC50 about 54,458 μg/ml and 4,768 μg/ml for vitamin C. The statistical test result of antioxidantactivity shows that there is no any significant difference. The TLC result shows that compoundcontained in etanolic extract of citrus aurantifolia are flavonoid and Vitamin C.Keywords: Citrus aurantifolia extract, DPPH method, antioxidant and IC50.